Treatment Adherence as a New Choice Factor for Optimization of Oral Anticoagulation Therapy in Patients with Atrial Fibrillation and Hemostatic Gene Polymorphisms - Yu. P. Skirdenko; A. V. Shustov; V. V. Zherebilov; N. A. Nikolayev (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate treatment adherence and prevalence of CYP2C9 and VKORC1 gene mutations in patients with atrial fibrillation (AF) and provide rationale of choice for oral anticoagulation therapy.Material and methods. Treatment adherence was evaluated in 137 AF patients (aged 35-85 years) with quantitative estimation of drug therapy adherence along with compliance to medical support and lifestyle modifications. Among them 82 patients underwent polymerase chain reaction (PCR) analysis of CYP2C9 and VKORC1 gene polymorphisms.Results. Patients receiving anticoagulation therapy are characterized by lower level of adherence compared to patients without anticoagulants (65.2±19.3% vs 68.5±19.1%; Wald-Wolfowitz; p<0.05). Considering all studied parameters men are less adherent than women (54.7±18.6% vs 60.6±16.7%; Kolmogorov-Smirnov; p<0.05). Patients receiving new oral anticoagulants (NOAC) have better compliance compared with patients of warfarin group. Mutations in CYP2C9 gene were detected in 32.9%, VKORC1 – in 68.3%, and their combination – in 21.9% of study participants. Warfarin therapy may be potentially dangerous in such patients due to low adherence.Conclusion. Considering high prevalence of CYP2C9 and VKORC1 gene mutations treatment adherence should be estimated to optimize choice of anticoagulation therapy. NOAC treatment should be considered in patients with low adherence for prevention of thromboembolic complications.